Pengaruh Kebijakan, Regulasi, dan Anggaran Terhadap Perkembangan Kapasitas PLTS di Australia - Kusnandar, Giusna Dipankara; Satya Kumara, I Nyoman; Sukerayasa, I Wayan (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i02.P08, 2021)
Australia is one of the countries with the highest solar PV capacity in the world. The capacity of solar PV installed in Australia has reached 16,319 MW and 600 W per capita at the end of 2019, making Australia the country with the highest per-capita capacity in the world. The Australian Government has established policies, regulations, and budgets as commitments to support the achievement of the solar PV capacity. This paper reviews and analyzes policies, regulations, and funds in Australia from federal to state levels on the side of solar PV development. Analysis showed that policies and regulations supported by the suitability of the government budget have a consequential effect on increasing the capacity of solar PV to implement and realize renewable energy targets in Australia. Several policies aforementioned as Feed-in Tariff, RET, NSSP, and budgets that focus on R&D have a significant impact on increasing the capacity of solar PV installed. Thus, realistic targets that are phased in, structured policy and regulatory support, budget compliance, and continuous education to the public are essential aspects that could be adopted in Indonesia to accelerate the realization of the national solar PV capacity target.